Peut-on trouver trace de la Loi islamique dans les documents arabes chrétiens de Tolède des XIIe et XIIIe siècles? - Jean-Pierre Molénat (Medievalista)
During the 12th and 13th centuries, Toledo´s notarial diplomas certify the persistent Arabization of city Christian populations, traditionally designated as Mozarabic. Not only the script and the and the language of those diplomas are effectively Arabic, but also the used formulas, starting by the initial basmala (God´s invocation), have the origin in the Muslim notarial practice. The featured witnesses are “professional witnesses”, and here one is able to find some of the city’s prominent personalities, who certify have seen and heard both parties establish the contract. That said, the contract celebration is situated in a recent past, and not in the present, as it occurs with the notarial acts form the non-Arab Christian population from the same period. Yet, over and above the formal issues, it is not easy to find a direct influence of the Islamic law in those diplomas. Even an expression of Arab origin as evident as «marjadraque» [marǧi‘al-darak] it does not necessarily addresses to any Islamic law rule, as that guarantee was already assured in the Visigoths’ law. Also, the clauses of the matrimonial contracts or family shares, are more as per the Fuero Juzgo than the Islamic law. Although the enormous Arab influence in the “Mozarabic Christians” from Toledo, which actually lasted more than two centuries after city´s Christian conquer, it is not possible to find testimonies that prove the influence of the Islamic law over them.